2022
DOI: 10.1097/brs.0000000000004409
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility Analysis of Neoadjuvant Teriparatide Therapy in Osteopenic Patients Undergoing Adult Spinal Deformity Surgery

Abstract: Study Design. A cost-utility analysis study. Objective. This study aims to evaluate the cost-utility of neoadjuvant teriparatide therapy in osteopenic patients undergoing adult spinal deformity (ASD) surgery. Summary of Background Data. There is increasing evidence supporting preoperative use of anabolic agents such as teriparatide for preoperative optimization of ASD patients with poor bone density. However, such treatments are associated with added costs. To our knowledge, the cost-utility of teriparatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Preoperative interventions for smoking cessation, weight loss, depression, diabetes management, blood pressure control, and osteoporosis have all shown benefits in terms of minimizing complication rates and maximizing clinical improvement after spinal surgery. 27,43,44 Raad et al 44 found that four-month preoperative intervention of teriparatide in osteopenic patients was both clinically effective and cost-effective, mitigating the occurrence of pseudarthrosis and PJF. Our results build on this previous literature by helping clinicians prioritize those factors that may be of greatest import in the perioperative period and those which might preclude surgical intervention until properly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative interventions for smoking cessation, weight loss, depression, diabetes management, blood pressure control, and osteoporosis have all shown benefits in terms of minimizing complication rates and maximizing clinical improvement after spinal surgery. 27,43,44 Raad et al 44 found that four-month preoperative intervention of teriparatide in osteopenic patients was both clinically effective and cost-effective, mitigating the occurrence of pseudarthrosis and PJF. Our results build on this previous literature by helping clinicians prioritize those factors that may be of greatest import in the perioperative period and those which might preclude surgical intervention until properly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has also been demonstrated that treatment with teriparatide analogs may reduce PJK rates from 15.2% to 4.6% in adult spinal deformity patients. 6 It is worth noting that despite the substantial costs of some of these treatments, they have been demonstrated to be cost-effective in 82% of patients with osteopenia, according to a study by Raad et al 7…”
Section: Osteoporosis and Proximal Junctional Kyphosismentioning
confidence: 99%
“…Firstly, there is a substantial body of evidence in Japan demonstrating the beneficial effects of TPTD in patients with osteoporosis who undergo spinal fusion surgery [41][42][43][44][45]. Additionally, neoadjuvant TPTD has been reported to be a cost-effective strategy for reducing post-operative complications in patients with osteopenia undergoing adjacent segment degeneration surgery [47]. Secondly, Japan has a comprehensive healthcare insurance system, the National Health Insurance system.…”
Section: Trends and Factors In The Selection Of Osteoporosis Treatmen...mentioning
confidence: 99%